KONTRIBUSI KEBIASAAN MEMBACA DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 2 PADANG - Riki Zakaria, Fitra Afrida Amna (Menara Ilmu, 2018)
The low ability of writing expositional texts, low reading habits, and the motivation ofstudents in grade X SMA Negeri 2 Padang behind this research. The purpose of the studydescribes the amount of the contribution of reading habits and motivation to learn the abilityto write exposition of text students of class X SMA Negeri 2 Padang. The research type isquantitative by using descriptive method and correlation design with population 274 peopleand sample 74 students. Sampling technique is done by random sampling. The instrument ofthis research is questionnaire and performance test. Technique analyze research data usingPearson Product Moment correlation test (PPM), double correlation test, t test, F test, anddeterminant coefficient formula. The results of the study illustrate that there is a habit ofreading and motivation to learn together to contribute and a significant relationship to theability to write exposition class X SMA 2 Padang.Keywords: Reading Habit, Learning Motivation, Writing Ability